IDENTIFIKASI METABOLIT SEKUNDER BRUCEA JAVANICA (L) MERR DI PULAU TIMOR MELALUI UJI FITOKIMIA - Jois Moriani Jacob; Yanse Yanne Rumlaklak (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2020)
Brucea javanica (L) Merr is a shrub that has various types of secondary metabolites that have pharmacologic effects. Various studies on this plant in Indonesia have been conducted, but research on secondary metabolites that have the potential as herbal medicines from this plant originating from the island of Timor has never been done. Therefore, this study aims to evaluate secondary metabolites found in Brucea javanica (L) Merr which originates from Timor Island. Samples in the form of roots, stems, leaves, seeds, and flowers of plants are sent to the Indonesian Institute of Sciences (LIPI) to identify these plant species. Plant determination is carried out under the determination procedure in the LIPI ethnobotany laboratory. The plant determination test results showed that the plant samples sent were Brucea javanica (L) Merr. While the phytochemical tests were carried out at the Laboratory of Chemistry at the Faculty of Science and Engineering of the University of Nusa Cendana to identify secondary metabolites from the Brucea javanica (L) Merr plant according to the phytochemical test standards in the Undana Chemistry laboratory. Phytochemical tests show that there are 4 secondary metabolites found in Brucea javanica (L) Merr namely Alkaloids (+), Tannins (+++), Saponins (+), and Triterpenoids (+++) while secondary metabolites such as Flavonoids and Steroids are not contained in this plant.